Bio-ecological factors associated with the psychological distress of fathers of children with Autism Spectrum Disorder: a population-based study of Australian families - Wood, Catherine; Seymour, Monique; Giallo, Rebecca (My University, 2017)
Using a bio-ecological framework, the aim of this study was to examine factors associated with psychological distress experienced by fathers of children with autism spectrum disorder from a nationally representative sample of Australian children and their families. Individual (e.g. age and self-efficacy), interpersonal (e.g. partner distress, couple relationship, child behaviour and social support) and social environmental factors (e.g. job quality and financial hardship) were explored as potential predictors of fathers’ distress. Data were drawn from the Longitudinal Study of Australian Children, where 159 fathers of children with autism spectrum disorder were identified. As comparison, 6578 fathers of children without developmental disabilities were identified. Multiple regression analyses showed that experiencing depression within the past year, job quality (e.g. autonomy and access to parental leave) and social support were significant predictors for fathers of children with autism spectrum disorder. The importance of supporting the well-being of fathers of children with autism spectrum disorder is discussed.
Autism
Keywords: Health -- Disability; Families -- Fathers; Families and relationships; Health and wellbeing; Families; Health; Disability; Fathers; Families and relationships; Health and wellbeing